The Development Of Computational Model Through Reverse Engineering : Side Mirror Case Study - Mat, Shafizal; Salim, Mohd Azli; Mahmud, Jamaluddin; Saedon, Juri (Universiti Teknikal Malaysia Melaka, 2009)
Reverse engineering is a process of capturing the geometry by existing physical objects and used the data obtained as a foundation for re-designing or designing something new.Laser scanners are commonly used since they can be a sample of three dimensional range images fast and very accurately relative to other technologies.The complexity of the process to re-modelling the objects is very obvious since the re-shaping of the object is more to surface consideration and not solid modelling.This paper employs and compares two methods of reverse engineering.First,conventional method is used where the parts of a car side mirror are drawn from direct measurement.Second,the detail drawings of the same parts are generated through three-dimensional scanning software.For the conventional method,direct measurements are obtained using a vernier calliper,ruler and micrometer.For the later approach,three-dimensional scanning software is used,where the side mirror and its components are scanned to obtain the initial feature, which later on is refined to achieve an accurate computational model.Based on the final computational model,both methods are compared and analysed.This paper is aimed to exhibit a computer aided reverse engineering approach in modelling a product through both methods.A comprehensive methodology is presented through a case study approach.